Association between immunohistochemical expression of matrix metalloproteinases and metastasis in oral squamous cell carcinoma: Systematic review and meta‐analysis. Issue 3 (21st November 2019) - Miguel, Andressa F. P.; Mello, Fernanda W.; Melo, Gilberto; Rivero, Elena R. C.
Abstract: Background: The aim of this systematic review (SR) was to summarize and critically appraise available evidence on the association of the immunohistochemical expression of matrix metalloproteinases (MMPs) with the occurrence of lymph node/distant metastasis of oral squamous cell carcinoma (OSCC). Methods: Searches were conducted in five main electronic and three gray literature databases. Results: From 2128 records identified, 50 were included for qualitative analysis. A total of 12 MMPs were identified (‐1, ‐2, ‐3, ‐7, ‐8, ‐9, ‐10, ‐11, ‐13, ‐25, ‐26, and MT1‐MMP). Most included studies reported a positive association of MMP‐1, ‐2, ‐3, ‐7, ‐9, and MT1‐MMP with lymph node metastasis. MMP‐8, ‐25, and ‐26 were not associated with lymph node metastasis. Conclusions: According to this SR, MMP‐1, ‐2, ‐3, ‐7, ‐9, and MT1‐MMP seem to play an important role in lymph node metastasis of OSCC.